DIFFERENTIAL LEVELS OF CYTOKINES AND INTERCELLULAR ADHESION MOLECULES AND THEIR DIAGNOSTIC EFFICIENCY IN AUTOIMMUNE AND ONCOLOGICAL THYROID DISEASES - S. P. Kazakov (Медицинская иммунология, 2014)
The article presents novel data concerning measurements of cytokine levels (IFNγ, IL-4, IL-6, IL-10, TNFβ, MCP-1), and cell adhesion molecules (sE-Selectin, sICAM-1) in blood plasma, llike as parameters of their diagnostic efficiency in the patients with thyroid autoimmune diseases (TAD), thyroid adenoma and cancer. The cytokines were analyzed by flow cytometris technique. We have shown that IL-4, IL-6, TNFβ, MCP-1 cytokines play an important role in pathogenesis of TAD, especially IL- 6, MCP-1. In cases of thyroid adenoma, a sufficient role belongs to IL-6, IL-10, TNFβ, MCP-1, sICAM-1, with IL-6 и sICAM-1 showing most significant changes. In thyroid cancer, IL-6, IL-10, MCP-1, sE-seleсtin are informative, with sE-seleсtin being the most reliable marker. In differential diagnostic between thyroid cancer and autoimmune diseases, one should employ such cytokines, as IL-10, MCP-1, sE-seleсtin, the latter being most significant. Differential diagnostics between thyroid adenoma and autoimmune diseases suggests determination of IL-6, IL-10 and sICAM-1 levels, preferring IL-6 and sICAM-1for their better diagnostic efficiency. Threshold levels of IL-6, sE-seleсtin may discriminate between thyroid cancer and adenoma, but these differences are of poor diagnostic efficiency.